Desenvolvimento de método analítico para determinação de multimicotoxinas em leites - Morais, Danielly Nascimento (2019)
This work aimed to develop and validate an analytical method to determine multimicotoxins (aflatoxins B1 - AFB1, G1 - AFG1, G2 - AFG2 and M1 - AFM1, ochratoxin - OTA and zearalenone - ZEA) in fluid milk using detector - coupled liquid chromatography. fluorescence The chromatographic parameters were defined by sequential designs. The mobile phase, acetonitrile and 0.85% acidified water (30:70) and acetonitrile, methanol and 0.85% acidified water (50:10:40) were defined using mix planning. The flow rate of 1.4 mL / min was defined by fractional factorial design which allowed the subsequent application of a Central Rotational Composite Design (DCCR). Through DCCR, optimal asymmetry values were obtained for all mycotoxins within the range of 1.0 and 1.5, considered ideal for chromatographic peaks. The desired resolution of 2.80 between the ZEA and OTA peaks was obtained through the desirability function which indicated the conditions for the parameters: mobile phase acidification, column temperature and injection volume to be 0.85%, 35 ºC and 35 µL, respectively. In parallel, an extraction method based on the QuEChERS method was developed. The method was validated, the quantification limit (LQ) were 0.16; 1.08; 0.01; 0.12; 0.33 and 8.93 µg.Kg-1 for AFM1, AFB1, AFG1, AFG2, OTA and ZEA, respectively. Method recovery ranged from 73 to 114%. Subsequently, the method was applied to evaluate the occurrence of multimicotoxins in fluid milk (n = 30) sold in the city of Medianeira, Western Paraná. The presence of AFB1, AFG1, AFG2 and AFM1 was detected in 26%, 30%, 93% and 80% of the analyzed samples, respectively; However, the presence of AFM1 was below the maximum limit allowed by Brazilian legislation (0.5 µg.Kg-1). No OTA and ZEA were found in the analyzed samples. Therefore, the method was efficient to identify and quantify multimicotoxins in fluid milk and can be applied as a routine method to monitor milk quality, aiming to offer safe and quality products for human consumption.